2015
DOI: 10.1007/s00299-015-1787-8
|View full text |Cite
|
Sign up to set email alerts
|

Activated expression of AtWRKY53 negatively regulates drought tolerance by mediating stomatal movement

Abstract: AtWRKY53 is an early factor in drought response and activated expression of AtWRKY53 regulates stomatal movement via reduction of H 2 O 2 content and promotion of starch metabolism in guard cells. Drought is one of the most serious environmental factors limiting the productivity of agricultural crops worldwide. However, the mechanisms underlying drought tolerance in plants remain unclear. AtWRKY53 belongs to the group III of WRKY transcription factors. In this study, we observed both the mRNA and protein produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 56 publications
4
69
1
2
Order By: Relevance
“…The nucleus localization after translation and the up-regulated expression pattern upon drought and exogenous ABA indicates that TaWRKY1 is possibly involved in mediating drought responses through an ABA-dependent pathway. Several lines of evidence have shown that a subset of the WRKY family genes are functional in mediating plant tolerance to drought stress, through their roles in modulating the physiological processes associated with defensiveness of drought or related osmotic stresses (Ishiguro and Nakamura 1994;Niu et al 2012;Wang et al 2013;Sun and Yu 2015;Jia et al 2015). For instance, TaWRKY2, TaWRKY19, and TaWRKY10, the WRKY family genes in wheat, function effectively in responses to a set of abiotic stresses, such as drought, high salinity, low temperature, wounding, and the external ABA application via improvement of osmolyte accumulation and cellular ROS homeostasis (Niu et al 2012;Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleus localization after translation and the up-regulated expression pattern upon drought and exogenous ABA indicates that TaWRKY1 is possibly involved in mediating drought responses through an ABA-dependent pathway. Several lines of evidence have shown that a subset of the WRKY family genes are functional in mediating plant tolerance to drought stress, through their roles in modulating the physiological processes associated with defensiveness of drought or related osmotic stresses (Ishiguro and Nakamura 1994;Niu et al 2012;Wang et al 2013;Sun and Yu 2015;Jia et al 2015). For instance, TaWRKY2, TaWRKY19, and TaWRKY10, the WRKY family genes in wheat, function effectively in responses to a set of abiotic stresses, such as drought, high salinity, low temperature, wounding, and the external ABA application via improvement of osmolyte accumulation and cellular ROS homeostasis (Niu et al 2012;Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been noted that the drought response of plants is associated with the function exerted by a suite of WRKY proteins. For example, Arabidosis AtWRKY53 acts as a significantly negative regulator in drought response through modulation of stomata movement, cellular H 2 O 2 accumulation, and starch biosynthetic metabolism (Sun and Yu 2015). TaWRKY2 and TaWRKY19, two WRKY family genes of wheat, mediate drought tolerance of plants via activation of STZ and DREB2A, two conserved components of the osmotic stress-defensive pathways (Niu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, AtWRKY53 and AtWRKY70 play a positive role in SA-mediated resistance to P . syringae infection [43,44], and OsWRKY45 acts in the SA signaling pathway independently of NPR1 . Our results showed that the expression levels of NPR1 and WRKY45 were reduced in oscol9-ko plants, indicating that OsCOL9 possibly acted upstream of NPR1 (Fig 6A).…”
Section: Discussionmentioning
confidence: 99%
“…The stomatal closure assay was performed using leaves harvested from 30-day-old control or transgenic tobacco seedlings as described previously [24]. The leaves were immersed in a solution containing 10 mM KCl, 50μM CaCl 2 , and 10 mM MES-KOH (pH 6.15) under strong light for 6 h. Subsequently, 50 μM ABA or 200 mM mannitol was added to the solution.…”
Section: Methodsmentioning
confidence: 99%